2021
DOI: 10.1002/ajim.23278
|View full text |Cite
|
Sign up to set email alerts
|

Cancer survival among World Trade Center rescue and recovery workers: A collaborative cohort study

Abstract: Background World Trade Center (WTC)‐exposed responders may be eligible to receive no‐cost medical monitoring and treatment for certified conditions, including cancer. The survival of responders with cancer has not previously been investigated. Methods This study compared the estimated relative survival of WTC‐exposed responders who developed cancer while enrolled in two WTC medical monitoring and treatment programs in New York City (WTC‐MMTP responders) and WTC‐exposed responders not enrolled (WTC‐non‐MMTP res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…In summary, we report a doubling in risk of overall MGUS and an over 3.5-fold elevated risk of light-chain-MGUS suggesting unambiguous associations between environmental exposures present at the WTC disaster site and myeloma precursor disease. Recently, it was reported that rescue/recovery worker cancer patients enrolled in a WTC Health Program had improved survival relative to the New York state population, potentially due to reduced barriers to systematic health surveillance and treatment and no out-of-pocket medical care costs [ 31 ]. While a randomized controlled trial examining the risks and benefits of MGUS screening is ongoing and will provide clearer guidance on public health recommendations [ 32 ], if improved survival among MGUS screened cohorts is demonstrated, the important findings from our current study provide evidence that screening of WTC-exposed cohorts should be recommended.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, we report a doubling in risk of overall MGUS and an over 3.5-fold elevated risk of light-chain-MGUS suggesting unambiguous associations between environmental exposures present at the WTC disaster site and myeloma precursor disease. Recently, it was reported that rescue/recovery worker cancer patients enrolled in a WTC Health Program had improved survival relative to the New York state population, potentially due to reduced barriers to systematic health surveillance and treatment and no out-of-pocket medical care costs [ 31 ]. While a randomized controlled trial examining the risks and benefits of MGUS screening is ongoing and will provide clearer guidance on public health recommendations [ 32 ], if improved survival among MGUS screened cohorts is demonstrated, the important findings from our current study provide evidence that screening of WTC-exposed cohorts should be recommended.…”
Section: Discussionmentioning
confidence: 99%
“…The availability of the WTC Health Program at no out-of-pocket cost to enrollees also might have impacted cancer-specific mortality. Being enrolled in the WTC Health Program has been associated with lower cancer-specific mortality in RRW, 5 and individuals with self-reported 9/11-related physical or mental health conditions have been targeted in outreach efforts to increase WTC Health Program enrollment. 38 When we stratified the post-9/11 group by enrollee group, we observed that witnessing ≥3 traumatic events was associated with a 2-fold increased risk in RRW, which was similar in magnitude to the association between PTSD and non-cancer mortality in this enrollee group and aligns with previous research in the WTCHR that has found witnessing traumatic events on 9/11 to be a major predictor of PTSD.…”
Section: Discussionmentioning
confidence: 99%
“…We conducted sensitivity analyses in the post‐9/11 group by repeating the fully adjusted model for the association between 9/11‐related exposure and mortality in the following subgroups: (1) Excluding those aged ≥65 years on 9/11/2001 to capture potential premature mortality; (2) excluding firefighters and police responders affiliated with the Fire Department of New York City (FDNY) and the New York City Police Department (NYPD), respectively, because previous research suggests lower rates of PTSD 31 and higher survival 5 in traditional versus non‐traditional responders (defined elsewhere 32 ); and (3) excluding those with multiple cancers because subsequent cancer may have a worse survival rate than the first. Statistical analyses were performed using SAS, v9.4 (SAS Institute Inc.).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As an intervention, Goldfarb et al (2021) compared survival among cancer patients in three groups: responders enrolled in medical monitoring and treatment programs in New York City (NYC, the treatment group); responders who do not participate in the NYC programs; and New York State cancer patients who are not in the responder group. 54 Survival was improved among the treatment group compared with either control group after adjusting for demographic factors and temporal trends. This suggests that participating in treatment offered at no-cost by the WTC Health Program may benefit survival among cancer patients.…”
Section: Special Issue: Examples Of New Researchmentioning
confidence: 90%